Moiré engineering in 2D heterostructures with process-induced strain - Peña, Tara; Dey, Aditya; Chowdhury, Shoieb A.; Azizimanesh, Ahmad; Hou, Wenhui; Sewaket, Arfan; Watson, Carla; Askari, Hesam; Wu, Stephen M. (Applied physics letters, 2023)
We report deterministic control over a moiré superlattice interference pattern in twisted bilayer graphene by implementing designable device-level heterostrain with process-induced strain engineering, a widely used technique in industrial silicon nanofabrication processes. By depositing stressed thin films onto our twisted bilayer graphene samples, heterostrain magnitude and strain directionality can be controlled by stressor film force (film stress × film thickness) and patterned stressor geometry, respectively. We examine strain and moiré interference with Raman spectroscopy through in-plane and moiré-activated phonon mode shifts. Results support systematic C3 rotational symmetry breaking and tunable periodicity in moiré superlattices under the application of uniaxial or biaxial heterostrain. Experimental results are validated by molecular statics simulations and density functional theory based first principles calculations. This provides a method not only to tune moiré interference without additional twisting but also to allow for a systematic pathway to explore different van der Waals based moiré superlattice symmetries by deterministic design.